Bacteriological quality of drinking water and its associated factors in Ethiopia: A systematic review and meta-analysis. - Chala Daba; Leykun Berhanu; Belay Desye; Gete Berihun; Abebe Kassa Geto (PLoS ONE)
Introduction Drinking contaminated water is a significant cause of mortality and morbidity in Sub-Saharan Africa, where access to safe drinking water is limited. Although numerous studies have investigated the bacteriological quality of drinking water in Ethiopia, their findings have been inconsistent and varied, hindering the implementation of effective water quality monitoring. Moreover, there is a lack of nationwide assessment of the bacteriological quality of drinking water in Ethiopia. Therefore, this systematic review and meta-analysis aimed to determine the bacteriological quality of drinking water and its associated factors in Ethiopia. Methods An international electronic database, including PubMed, Science Direct, Global Health, CINAHL, African Journals Online, HINARI, and Google Scholar was employed to retrieve the relevant articles. The study adhered to the Preferred Reporting Items for Systematic Reviews and Meta-Analyses Protocols (PRISMA) guidelines. A random-effects model was used to estimate the pooled effect size, and the Egger regression model was employed using STATA 14 software to assess potential publication bias. Results A total of 26 studies involving 7,962 water samples met the eligibility criteria for meta-analysis. The pooled prevalence of at least one bacteriological contamination of drinking water was 52.26% (95%CI: 39.09-65.43), with extreme heterogeneity (I2 = 99.7%; p-value < 0.001). The pooled prevalence of total and fecal coliform in drinking water was 49.55% (95% CI: 34.88-64.23) and 44.27% (95%CI: 34.36-54.19), respectively. 14.13% of the water source was at a very high sanitary risk level (unfit for drinking), with significant heterogeneity (I2 = 94.1%, p< 0.001). The absence of household-level water treatment (OR = 3.3; 95%CI: 1.28-5.32) and drawing water using dipping methods (OR = 4.52; 95%CI: 1.71-7.34) were determinant factors for bacteriological contamination of drinking water. Conclusion We found that the bacteriological quality of drinking water did not comply with the World Health Organization and Ethiopia's standard guidelines for drinking water, which call for urgent intervention. One out of seven water sources was at a high sanitary risk level, which could increase the risk of infectious disease in the country. The absence of household-level water treatment and drawing water using dipping was a significant factor in the bacteriological quality of drinking water. Based on these findings, the water supply and sewerage authority should prioritize regular monitoring of the bacteriological quality of drinking water.